APLIKASI PLUGIN TRANSFER DOMAIN DI PT BEON INTERMEDIA - Arifin, Samsul; Krisnadita, Yolanda (JURNAL TEKNOLOGI INFORMASI: Teori, Konsep, dan Implementasi, 2017)
PT. Beon Intermedia specializes in hosting and domain services. High reputation requires PT. Beon Intermedia to always work quickly and efficiently. But there are still obstacles in the Domain displacement activity, namely in the recording and checking for Domain transfer activities are still using conventional methods that take up to 7 days workmanship.To solve this problem, so we try a solution for an application / plugin that is embedded in the system in PT. Beon Intermedia. The plugin works automatically and continuously to the process for switching domain, check the status of the transfer and perform notifications. The plugin works in a way to grab the data from the system regristrar to update the progress status of the domain that you want to move. Our results, this plugin goes well, the process of switching domain by using this plugin can cut the time domain displacement of an advanced first 7 days to 4 days, so that the service becomes faster, recorded in the system and to work more efficiently.Â Keywords: Plugin, Domain Transfer